YES We show the termination of the TRS R: ap(ap(ff(),x),x) -> ap(ap(x,ap(ff(),x)),ap(ap(cons(),x),nil())) -- SCC decomposition. Consider the dependency pair problem (P, R), where P consists of p1: ap#(ap(ff(),x),x) -> ap#(ap(x,ap(ff(),x)),ap(ap(cons(),x),nil())) p2: ap#(ap(ff(),x),x) -> ap#(x,ap(ff(),x)) p3: ap#(ap(ff(),x),x) -> ap#(ap(cons(),x),nil()) p4: ap#(ap(ff(),x),x) -> ap#(cons(),x) and R consists of: r1: ap(ap(ff(),x),x) -> ap(ap(x,ap(ff(),x)),ap(ap(cons(),x),nil())) The estimated dependency graph contains the following SCCs: {p1, p2} -- Reduction pair. Consider the dependency pair problem (P, R), where P consists of p1: ap#(ap(ff(),x),x) -> ap#(ap(x,ap(ff(),x)),ap(ap(cons(),x),nil())) p2: ap#(ap(ff(),x),x) -> ap#(x,ap(ff(),x)) and R consists of: r1: ap(ap(ff(),x),x) -> ap(ap(x,ap(ff(),x)),ap(ap(cons(),x),nil())) The set of usable rules consists of r1 Take the reduction pair: matrix interpretations: carrier: N^4 order: lexicographic order interpretations: ap#_A(x1,x2) = ((1,0,0,0),(0,0,0,0),(0,1,0,0),(0,0,1,0)) x1 + ((1,0,0,0),(1,0,0,0),(0,1,0,0),(0,0,1,0)) x2 ap_A(x1,x2) = ((0,0,0,0),(0,0,0,0),(1,0,0,0),(1,0,0,0)) x1 + ((0,0,0,0),(0,0,0,0),(1,0,0,0),(0,0,0,0)) x2 + (0,0,1,1) ff_A() = (3,1,1,1) cons_A() = (1,1,1,0) nil_A() = (1,1,1,1) The next rules are strictly ordered: p1 We remove them from the problem. -- SCC decomposition. Consider the dependency pair problem (P, R), where P consists of p1: ap#(ap(ff(),x),x) -> ap#(x,ap(ff(),x)) and R consists of: r1: ap(ap(ff(),x),x) -> ap(ap(x,ap(ff(),x)),ap(ap(cons(),x),nil())) The estimated dependency graph contains the following SCCs: {p1} -- Reduction pair. Consider the dependency pair problem (P, R), where P consists of p1: ap#(ap(ff(),x),x) -> ap#(x,ap(ff(),x)) and R consists of: r1: ap(ap(ff(),x),x) -> ap(ap(x,ap(ff(),x)),ap(ap(cons(),x),nil())) The set of usable rules consists of (no rules) Take the reduction pair: matrix interpretations: carrier: N^4 order: lexicographic order interpretations: ap#_A(x1,x2) = ((1,0,0,0),(1,1,0,0),(1,0,1,0),(1,1,1,1)) x1 + ((1,0,0,0),(1,1,0,0),(0,0,1,0),(1,1,1,1)) x2 ap_A(x1,x2) = ((1,0,0,0),(1,1,0,0),(1,1,1,0),(1,1,1,1)) x2 + (1,1,1,1) ff_A() = (1,1,1,1) The next rules are strictly ordered: p1 We remove them from the problem. Then no dependency pair remains.